Brassinosteroids are involved in ethylene‐induced Pst DC3000 resistance in Nicotiana benthamiana. (17th December 2019) - Xiong, J.; He, R.; Yang, F.; Zou, L.; Yi, K.; Lin, H.; Zhang, D.
Abstract: Plant immunity is regulated by a huge phytohormone regulation network. Ethylene(ET) and brassinosteroids (BRs) play critical roles in plant response to biotic stress; however, the relationship between BR and ET in plant immunity is unclear. We used chemical treatments, genetic approaches and inoculation experiments to investigate the relationship between ET and BR in plant defense against Pst DC3000 in Nicotiana benthamiana . Foliar applications of ET and BR enhanced plant resistance to Pst DC3000 inoculation, while treatment with brassinazole (BRZ, a specific BR biosynthesis inhibitor) eliminated the ET induced plant resistance to Pst DC3000. Silencing of DWARF 4 (DWF4, a key BR biosynthetic gene), BRASSINOSTEROID INSENSITIVE 1 ( BRI1, aBR receptor) and BRASSINOSTEROID-SIGNALING KINASE 1 ( BSK1, downstream of BRI1 ) also neutralised the ET‐induced plant resistance to Pst DC3000. ET can induce callose deposition and reactive oxygen species (ROS) accumulation to resist Pst DC3000, BRZ‐treated and gene‐silenced were completely eliminate this response. Our results suggest BR is involved in ET‐induced plant resistance, the involvement of ET in plant resistance is possibly by the induction of callose deposition and ROS accumulation, in a BR‐dependent manner. Abstract : Foliar applications of ET and BR enhanced plant resistance to Pst DC3000 inoculation, the involvement of ET in plant resistance possibly by the induction of callose deposite and ROS accumulation in a BR‐dependent way.